In vitro utilization of fructooligosaccharide by mutans streptococci (Pesquisa Odontológica Brasileira, 2001)
Neosugar is the trade name of a fructooligosaccharide (FOS) whose utilization by oral bacteria is not well known yet. The aim of the present study was to evaluate in vitro the effect of this product on the growth, fermentation and production of plaque by mutans streptococci: S. mutans, serotypes c, e and f, S. sobrinus, serotype d, S. downei, serotype h, S. cricetus, serotype a and S. rattus, serotype b. The evaluation of growth was carried out in Brain Heart Infusion (BHI) broths containing or not sucrose and FOS and in buffered broths having glucose or FOS as carbon sources, through optical density reading in spectrophotometer after 24 hours of incubation at 37ºC. Thereafter the reading of pH was made in the same media. The plaque produced on glass sticks in BHI broths containing 5% sucrose or FOS was weighed and carbohydrates and proteins were assayed. The possible cariogenicity of Neosugar was confirmed, since it sustained the same growth and intensity of fermentation of sucrose in BHI broth for all streptococci and permitted in vitro production of plaque by some of them. The amount of plaque as well as its content of proteins and carbohydrates were smaller than those produced with sucrose, although the difference was statistically significant only for carbohydrates.